Disparities in Posthospitalization Disposition Following Tracheotomy: A National Analysis - Radhika Duggal; Sarah Benyo; Elizabeth N. Dewey; Rebecca C. Nelson; Paul C. Bryson; Michael S. Benninger; Brandon Hopkins; William S. Tierney (OTO Open, 2025)
Abstract Objective Previous studies have demonstrated the impact of sociodemographic factors on disease development, management, and outcomes in adult and pediatric populations. Given that postoperative management is key in reducing complications following a tracheotomy, we assessed the impact of sociodemographic factors on a patient's discharge disposition. Study Design Cross‐sectional study. Setting Health Care Utilization Project's (HCUP) National Inpatient Survey (NIS). Methods The HCUP NIS was queried for all patients undergoing tracheotomy between 2017 and 2021. All analyses were performed using R Version 4.3.1 survey procedures to account for strata and cluster effects. Results We identified 81,069 admissions during which a tracheotomy was performed and, after appropriate weighting for the HCUP NIS survey design, found that 15.1% of admissions resulted in routine discharge, 4.5% transferred to a short‐term hospital, 52.3% transferred to a skilled nursing facility (SNF)/intermediate care facility (ICF)/other facility, 16.9% discharged with home health care. Admissions routinely discharged had the lowest median (interquartile range) age (48 [23, 61] years), whereas admissions resulting in death or transfer to a SNF/ICF/other facility type had the greatest age (63 [53, 70] years). On both univariable and multivariable analyses, age, race, sex, insurance type, geographic region, and hospital size were associated with discharge disposition. Conclusion Our study highlights that disparities exist among patient populations and were found in both unadjusted and adjusted analyses. Further attention and resource allocation for the care of patients with a tracheostomy may work toward identifying sources of disparity, which may be modified to improve patient care.